Effectiveness of Video as a Health Education Media for Adolescents' Attitudes Regarding Sexually Transmitted Infections (STIs) in Adolescents - Mustar, Mustar; Hasnidar, Hasnidar; Abbas, Hasriwiani Habo; Safitri, Nadia Nur (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
The increase in cases of sexually transmitted infections (STIs) has increased by more than one million cases worldwide every day. One of the vulnerable groups is that adolescents are the age group that is most at high risk of contracting sexually transmitted infections (STIs) because they are in a transition period characterized by high curiosity. So, at this age, it is always challenging to try new things without being accompanied by a good understanding and attitude about the actions taken. Therefore, health education from an early age is necessary in equipping adolescents with knowledge that impacts changing attitudes regarding Sexually Transmitted Infections (STIs). This study aims to analyze the influence of video media on adolescent attitudes about STIs at SMA Negeri 2 Takalar. This quantitative research method uses the quasi-experimental approach with a one-group pre-post test design. The population in this study was the student council of SMA Negeri 2 Takalar, which amounted to 22 students. The sampling technique in this study used a saturated sample; namely, the entire population became a sample in the study. Data collection techniques used were questionnaires distributed to respondents before and after treatment using video media. The data obtained were then analyzed using a paired sample t-test. The results showed that the value of the difference in the average value before and after health education using video was 9. 14 with a p-value = 0. 000 with a significance level of 0. 05. So it can be concluded that there is a significant influence of the use of video media on the attitudes of students with sexually transmitted infections. Therefore, the use of video media in conducting health education for students is highly recommended to create changes in adolescent attitudes regarding Sexually Transmitted Infections (STIs).